2006
DOI: 10.1039/b608453b
|View full text |Cite
|
Sign up to set email alerts
|

The reaction of tertiary phosphines with (Ph2Se2I2)2—the influence of steric and electronic effects

Abstract: The reaction of (Ph(2)Se(2)I(2))(2) with a wide variety of tertiary phosphines possessing different steric and electronic properties has been studied, leading in most cases to R(3)PSe(Ph)I adducts; [R(3)P = (p-CH(3)C(6)H(4))(3)P (1), (m-CH(3)C(6)H(4))(3)P (2), (o-OCH(3)C(6)H(4))(3)P (4), Ph(2)MeP (6), Me(2)PhP (7), Me(3)P (8), Cy(3)P (9)]. All of the products formed were characterised by elemental analysis, Raman and multinuclear NMR spectroscopy. Both steric and electronic factors are important in determining… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
20
0

Year Published

2007
2007
2016
2016

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 20 publications
(22 citation statements)
references
References 44 publications
2
20
0
Order By: Relevance
“…However, these are all lengthened when compared with the PvSe bonds of 2.1100(13) Å and 2.1115(12) Å in the structure of SeP( p-FC 6 H 4 ) 3 (which contains two independent molecules). 25 The P-Se bonds in 2, 3, 5 and 6 still have considerable double bond character, (sum of the single bond covalent radii of P and Se is 2.27 Å, compared to the sum of the double bond covalent radii, which is 2.09 Å), 17 and are shorter than typical single P-Se bonds observed for phenyl-seleno phosphonium cations [2.2189(15) to 2.2686( 18) Å], [26][27][28][29] or in phosphine adducts of selenium substituted N-heterocycles [2.284(1) to 2.327(1) Å]. 30 However, it should be noted that the P-Se bonds in 2, 3, 5 and 6 are similar in magnitude to those of 2.1659(18) to 2.1673(18) Å observed for the two independent…”
Section: Resultsmentioning
confidence: 93%
“…However, these are all lengthened when compared with the PvSe bonds of 2.1100(13) Å and 2.1115(12) Å in the structure of SeP( p-FC 6 H 4 ) 3 (which contains two independent molecules). 25 The P-Se bonds in 2, 3, 5 and 6 still have considerable double bond character, (sum of the single bond covalent radii of P and Se is 2.27 Å, compared to the sum of the double bond covalent radii, which is 2.09 Å), 17 and are shorter than typical single P-Se bonds observed for phenyl-seleno phosphonium cations [2.2189(15) to 2.2686( 18) Å], [26][27][28][29] or in phosphine adducts of selenium substituted N-heterocycles [2.284(1) to 2.327(1) Å]. 30 However, it should be noted that the P-Se bonds in 2, 3, 5 and 6 are similar in magnitude to those of 2.1659(18) to 2.1673(18) Å observed for the two independent…”
Section: Resultsmentioning
confidence: 93%
“…These structures are . 17 An excess of triphenylphosphine was added to the reaction mixtures resulting in the observation of additional peaks in the 31 P NMR spectrum. 12 Upon further investigation it was found that free PPh 3 was exchanging with the coordinated PPh 3 and that the rate of this exchange varied with the specific organochalcogen moiety being studied.…”
Section: Resultsmentioning
confidence: 99%
“…5c and d). [32][33][34][35][36][37] In the sole element of group 17 that is relevant to this perspective, the presence of three lone pairs and two bonding pairs at the acceptor iodine necessitates a linear geometry. The acceptor chemistry of molecular I 2 is not widely recognized and may appear unusual.…”
Section: Electronic Structure From Molecular Structurementioning
confidence: 99%